(untitled) (European Journal of Engineering Science and Technology, 2019)
This paper aimed to develop eco-friendly wall tiles from green color waste glass and local clay in Thailand. Owing to containing high fluxing agent, green glass cullet had been selected to develop wall tiles. It can reduce the sintering temperature of ceramic bodies. In addition, the green color of waste glass can promote the new texture of ceramic wall tiles. All materials used in this study consisted of green glass cullet (GGC), local ball clay (LBC), and local white clay (LWC). They were dried, milled, and sieved through a 50 mesh (297 micrometers) screen. Mixture formulations of materials had been conducted by using a tri-axial diagram. The rectangular specimens with dimension 50x100x7 mm were prepared by uniaxial pressing. They were all fired at 950oC with soaking for 1 h. Bending strength and water absorption of specimens were tested and compared with a Thai Industrial Standard (TIS 2508-2555). The results revealed that the formula contained 60% GGC, 30% LBC, and 10% LWC can achieve TIS 2508-2555. In addition, Scanning Electron Microscopy and X-Ray Diffraction technique were employed to characterize the microstructure of specimens. This can be summarized that utilizing waste glass and combining with local clay can develop eco-friendly fired clay wall tiles with light greenish brown texture.